Institutionalization of Swamp Buffalo Development in The Philippines - Cruz, L. c. (Proceeding INTERNATIONAL SEMINAR IMPROVING TROPICAL ANIMAL PRODUCTION FOR FOOD SECURITY)
The Asian swamp buffalo, representing 20.51% of the olds buffalo population, hasÂ played a major role as source of draft power in the production of major agricultural crops,and secondarily, as source of meat and milk among East and Southeast Asian countries forcenturies. In the past few decades, however, the intensification of crop farming, coupledwith increased farm mechanization, diminished the swamp uffaloes role as source of draftin small farms. Despite this development, their value as source of livelihood and foodremains high in small farm settings. To fully harness the potentials of this huge existinganimal resource to contribute to the growing demand for ruminant-derived products andmore importantly, to benefit the smallholders by way of increased income and access tonutritious food, the direction for its development can be shifted towards improving for meatand milk production. Genetic transformation is pursued thru cross breeding and sustainedbackcrossing with riverine buffalo breeds. For a wide-scale crossbreeding and geneticimprovement program to be achieved and sustained, a national policy has to be legislatedand the necessary program elements need to be institutionalized, including focused fundingand human resources. Critical elements include the establishment of National Gene Pool ofelite riverine buffaloes from where genetic materials for wide-scale crossbreeding will bederived. Complemented with a responsive AI system for maximum use of superior genetics.A scheme to stimulate village buffalo-based entrepreneurship with emphasis on the dairyaspect is essential in order to ensure ready market and increased income among small holdproducers. Further, essential components are relevant research and effective extensionservices.Â Key Words: Philippine Carabao, Swamp and Riverine Buffalo Crossbreeding, Small FarmEnterprise Development, Buffalo Meat and Milk Production